Various solvent effects on phytochemical constituent profiles, analysis of antioxidant and antidiabetic activities of Hopea parviflora. (February 2020) - Venkatachalam, Ranjitha; Kalimuthu, Kandasamy; Chinnadurai, Vajjiram; Saravanan, Mythili; Radhakrishnan, Ramalingam; Shanmuganathan, Rajasree; Pugazhendhi, Arivalagan
Graphical abstract: Highlights: in vitro antidiabetic study of Hopea parviflora . Hopea parviflora has the highest level of polyphenol and free radical scavenging activity. Methanol extracts showed the highest percentage reduction in blood glucose levels. Hopea parviflora - potential candidate for cost effective antidiabetic with less side effects. Abstract: The current research has been designed to assess the phytochemical composition, antioxidant and antidiabetic properties of Hopea parviflora, sequentially extracted with petroleum ether, chloroform, ethyl acetate, ethanol and methanol. All the five extracts were tested for qualitative and quantitative phytochemicals. DPPH, Superoxide, FRAP, ABTS and metal chelating antioxidant activities were evaluated. Antidiabetic potentials of all the five extracts were tested using standard in vitro α- amylase and α - glycosidase inhibition assays. Qualitative phytochemical screening showed the presence of alkaloids in all the extracts except petroleum ether and ethyl acetate. Steroids were present in the petroleum ether, ethyl acetate and chloroform extracts whereas glycosides were present in all the extracts, except ethanol. The total phenol, flavonoid, tannin and saponins contents varied from solvent to solvent, with the highest values being 18.9, 18.2, 0.98 and 39.9 mg/mL, respectively. Methanolic extract showed the highest antioxidant activities in DPPH, FRAP and superoxide assays. Moreover, effective results were observed for the ethanol and ethyl acetate extracts in the ABTS and metal chelating assays. The methanolic extract showed potential antidiabetic activities with the IC50 values of 230.2 and 308.2 μg/mL in α- amylase and α -glycosidase inhibition assays, respectively.